The Relevance of Ethics to Contemporary Management Education - Michal Weres (Communications of International Proceedings, 2025)
The article examines the role of ethics in contemporary management education, particularly in technical universities and programs like Engineering Management. In light of ongoing technological and social changes, it asks whether ethics should be treated as an essential managerial competence or merely as part of general education. Drawing on preliminary research the study analyzes students’ attitudes toward ethics and discusses challenges in teaching ethical content effectively. It argues that ethics should be meaningfully integrated into the curriculum – not only through isolated courses, but also via practical connections with other subjects. Given current challenges such as AI, sustainability, and digitalization, the article emphasizes the urgent need to develop ethical awareness among future managers and calls for a more strategic and interdisciplinary approach to ethics in higher education.
Keywords: management education; business ethics; ethics in management; higher education; ethical competencies